2011
DOI: 10.1111/j.1440-1843.2011.02047.x
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between COPD patients with and without alpha 1‐antitrypsin deficiency using an electronic nose

Abstract: An electronic nose can detect differences in smell prints of COPD patients with and without AAT deficiency. Augmentation therapy changes the volatile organic compound pattern. The electronic nose may be helpful in the diagnosis of AAT deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 34 publications
(83 reference statements)
0
46
0
Order By: Relevance
“…Hattesohl et al demonstrated that eNose derived VOCs profiles were not different between COPD patients with and without an alpha 1-antitrypsin (AAT) deficiency, after internal cross-validation. Moreover, cross-validated VOCs profiles of AAT deficiency patients did not differ after human recombinant AAT therapy [28]. …”
Section: Resultsmentioning
confidence: 99%
“…Hattesohl et al demonstrated that eNose derived VOCs profiles were not different between COPD patients with and without an alpha 1-antitrypsin (AAT) deficiency, after internal cross-validation. Moreover, cross-validated VOCs profiles of AAT deficiency patients did not differ after human recombinant AAT therapy [28]. …”
Section: Resultsmentioning
confidence: 99%
“…In principle, the diagnosis of ear, nose and throat infections [28] or pneumonia [29] is possible. Moreover, patients with lung cancer [30], asthma [31], COPD [18] or a 1 -AT deficiency [20] could be recognised when compared with healthy controls or individuals with other respiratory diseases. In our study, we aimed to test the hypothesis that OSAS could be recognised by its VOC profile and that the profile would change after CPAP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The participants breathed medicinal air (Aer medicinalis Linde; Linde Gas Therapeutics GmbH, Unterschleibheim, Germany) and exhaled for 10 s at a flow rate of 100-200 mL?s -1 into a disposable collection bag, which then was assessed within 60 s. This medicinal air was also used as reference air for the 60-s baseline, followed by a 60-s sample draw from the collection bag, and completed by a 60-s purging of the electronic nose. These measurements were performed in triplicate [20].…”
Section: Electronic Nosementioning
confidence: 99%
See 1 more Smart Citation
“…Electronic noses have been applied to various analysis fields such as food [33,34] and various diseases; diabetes [35], uremia [36], asthma [37], chronic obstructive pulmonary disease [38], pulmonary sarcoidosis [39], colorectal cancer [40], and malignant mesothelioma [41,42]. The application of electronic noses to detect lung cancer was also proposed.…”
Section: Discussionmentioning
confidence: 99%